Oncogenic signaling pathway dysregulation landscape reveals the role of pathways at multiple omics levels in pan-cancer - Wang, Na; He, Dan-Ni; Wu, Zhe-Yu; Zhu, Xu; Wen, Xiao-Ling; Li, Xu-Hua; Guo, Yu; Wang, Hong-Jiu; Wang, Zhen-Zhen (Frontiers in Genetics, 2022)
Dysregulation of signaling pathways plays an essential role in cancer. However, there is not a comprehensive understanding on how oncogenic signaling pathways affect the occurrence and development of cancer in pan-cancer. Here, we proposed a new method for identifying the role of oncogenic signaling pathways in pan-cancer by using the patient-specific pathways dysregulation models. Firstly, the pathways dysregulation profile was constructed by integrating typical oncogenic signaling pathways and the gene expression of TCGA samples, and four molecular subtypes with significant phenotypic and clinical differences induced by different oncogenic signaling pathways were identified. Then further multi-omics analysis, which characterizes the molecular differences among those subtypes, indicates that pathway-driven subtypes own unique molecular characteristics at each omics level. Several potential prognostic predictors which are closely related to the oncogenic signaling pathways were recognized by multi-omics level respectively, and can be targeted for the development of efficient treatment strategies and considered as biomarkers with potential therapeutic and prognostic significance for cancer. In summary, this study identified four different pathway-driven patterns presented as molecular subtypes and their related potential prognostic biomarkers by integrating multiple omics data. Our discovery provides a perspective for understanding the role of oncogenic signaling pathways in pan-cancer.